KERAGAMAN ISOLAT ACTINOMYCETES BERDASARKAN ANALISIS RFLP TERHADAP GEN NRPS - Nanik Sulistyani (Universitas Ahmad Dahlan, 2013)
Actinomycetes is one of the types of microorganisms that is essential for producing the active compounds, one of which is an antibiotic. Isolation of Actinomycetes from the rhizosphere of rice plant (Oryza sativa L.) and tin plant (Ficus carica L.) has yielded 13 isolates of antibiotic-producing Actinomycetes. This study aims to determine the diversity of isolates by RFLP analysis (Restriction Fragment Length Polymorphism) of the NRPS (Non Ribosomal Peptide Synthetase) gene. The study was carried out by isolating Actinomycetes isolate DNA and performed PCR on the 16SrRNA and NRPS genes. The RFLP analysis of the NRPS gene PCR products is then performed using the enzyme HaeIII. Identify the presence of DNA, the PCR product and RFLP results was performed by agarose gel electrophoresis. The diversity of isolates was analyzed by multivariate analysis. The results showed that the diversity of 13 isolates of Actinomycetes can be grouped into 5 groups: isolates 5 (group 1), isolates 8 (group 2), isolates 11 (group 3), isolates 6,7,9 (group 4) and isolates 1,2,3,4,10,12,13 (group 5).